Aberrant Salience Across Levels of Processing in Positive and Negative Schizotypy - Chun, Charlotte A.; Brugger, Peter; Kwapil, Thomas R. (Frontiers in Psychology, 2019)
Schizotypy is a multidimensional construct that is conceptualized as the expression of the underlying vulnerability for schizophrenia. Certain traits of positive schizotypy, such as odd beliefs, unusual perceptual experiences, suspiciousness, and referential thinking show associations with aberrant salience. Positive schizotypy may involve hyper-attribution of salience toward insignificant events, whereas negative schizotypy may involve hypo-attribution of salience, even toward important events. Attribution of salience is thought to involve dopamine-mediated processes, a mechanism that is disrupted in schizotypy; however, little is known about the cognitive processes potentially underlying salience attribution. The present study assessed the relationship between aberrant salience and latent inhibition, as well as their associations with positive and negative schizotypy. Salience was measured at various stages of processing, including visual salience, attributions of salience to contingency illusions, and self-reported experience of salience. Schizotypy symptoms were differentially associated with self-reported aberrant salience experiences: positive schizotypy showed positive associations and negative schizotypy showed inverse associations. However, neither schizotypy dimension was associated with visual salience, contingency illusions, or latent inhibition. Salience processing across perceptual, cognitive, and experiential levels likely involves different mechanisms, some of which may not show major disruption in subclinical manifestations of schizotypy.